K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

NV
1 tháng 9 2021

\(=xyz-xy-z\left(x+y\right)+x+y+z-1\)

\(=xy\left(z-1\right)-\left(x+y\right)\left(z-1\right)+z-1\)

\(=\left(z-1\right)\left(xy-x-y+1\right)\)

\(=\left(z-1\right)\left[x\left(y-1\right)-\left(y-1\right)\right]\)

\(=\left(x-1\right)\left(y-1\right)\left(z-1\right)\)

22 tháng 7 2015

A ) xy(z+y)+yz(y+z)+zx(z+x)

=y.[x(z+y)+z(y+z)]+zx(z+x)

=y.(xz+xy+zy+z2)+zx(z+x)

=y.(xz+z2+xy+zy)+zx(z+x)

=y.[z.(z+x)+y.(z+x)]+zx(z+x)

=y.(z+x)(z+y)+zx(z+x)

=(z+x)[y(z+y)+zx]

=(z+x)(yz+y2+zx)

B )xy(x+y)-yz(y+z)-zx(z-x)

=y.[x(x+y)-z(y+z)]-zx(z-x)

=y.(x2+xy-zy-z2)-zx(z-x)

=y.(x2-z2+xy-zy)-zx(z-x)

=y.[(x+z)(x-z)+y.(x-z)]-zx(z-x)

=y.(x-z)(x+z+y)+zx(x-z)

=(x-z)[y(x+z+y)+zx]

=(x-z)(yx+yz+y2+zx)

=(x-z)(yx+zx+yz+y2)

=(x-z)[x.(y+z)+y.(y+z)]

=(x-z)(y+z)(x+y)

 

30 tháng 6 2021

b. \(\text{ xy(x+y)-yz(y+z)-xz(z-x) =xy(x+y+z-z)+yz(y+z)+xz(x-z) =xy(x-z)+xy(y+z)+yz(y+z)+xz(x-z) =(x+y)(y+z)(x-z) }\)

22 tháng 8 2021

\(xyz-\left(xy+yz+xz\right)+\left(x+y+z\right)-1\)

\(=xyz-xy-yz+y-xz+x+z-1\)

\(=xy\left(z-1\right)-y\left(z-1\right)-x\left(z-1\right)+z-1\)

\(=\left(xy-y-x+1\right)\left(z-1\right)\)

\(=[\left(x-1\right)y-\left(x-1\right)]\left(z-1\right)\)

\(=\left(x-1\right)\left(y-1\right)\left(z-1\right)\)

30 tháng 7 2015

     xy( x+ y) + yz(y+z) + xz(x+z) + 3xyz

=   xy(x+y) + xyz + yz(y+z) +  xyz + xz(x+z) + xyz

= zy(x+y+z) + yz(x + y + z) + xz ( x+y+z)

 = ( x+ y +z )( xy + yz + zx) 

29 tháng 10 2016

\(xy\left(x+y\right)+yz\left(y-z\right)-xz\left(x+z\right)\)

\(=xy\left(x+y\right)+z\left[y\left(y-z\right)-x\left(x+z\right)\right]\)

\(=xy\left(x+y\right)+z\left(y^2-yz-x^2-xz\right)\)

\(=xy\left(x+y\right)+z\left[\left(y^2-x^2\right)-\left(yz+xz\right)\right]\)

\(=xy\left(x+y\right)+z\left[\left(y-x\right)\left(y+x\right)-z\left(x+y\right)\right]\)

\(=xy\left(x+y\right)+z\left(x+y\right)\left(y-z-x\right)\)

\(=\left(x+y\right)\left[xy+z\left(y-x-z\right)\right]\)

\(=\left(x+y\right)\left(xy-yz-xz-z^2\right)\)

19 tháng 7 2015

 

xy(x+y)-yz(y+z)-zx(z-x)

=y.[x.(x+y)-z.(y+z)]-zx.(z-x)

=y.(x2+xy-zy-z2)-zx.(z-x)

=y.[(x-z)(x+z)-y.(z-x)]-zx.(z-x)

=y.[-(z-x)(x+z)-y.(z-x)]-zx.(z-x)

=y.(z-x)(-x-z-y)-zx.(z-x)

=(z-x)(-xy-zy-y2-zx)

=(z-x)[-x.(y+z)-y.(y+z)]

=(z-x)(y+z)(-x-y)

=-(z-x)(y+z)(x+y)

 

30 tháng 9 2015

A=x2y+xy2+xyz+xyz+y2z+yz2+x2z+xyz+xz2-xyz

A=(x2y+xy2+xyz+y2z)+(yz2+x2z+xyz+xz2)

A=y(x2+xy+xz+yz)+z(yz+x2+xy+xz)

A=(y+z)(x2+xy+xz+yz)

A=(y+z)[x(x+y)+z(x+y)]

A=(y+z)(x+y)(x+z)

29 tháng 10 2016

xy(x+y) + yz(y-z) - zx(z+x)

=y[x(x+y)+z(y-z)]-zx(z+x)

=y(x2+xy+yz-z2)-zx(z+x)

=y(x2-z2+xy+yz)-zx(z+x)

=y[(x-z)(x+z)+y(x+z)]-zx(z+x)

=y[(x+z)(x-z+y)]-zx(z+x)

=(x+z)[y(x-z+y-zx)]

=(x+z)(xy-yz+y2-xyz)

22 tháng 10 2021

\(a,=\left(xy-1-x-y\right)\left(xy-1+x+y\right)\\ b,Sửa:a^3+2a^2+2a+1\\ =a^3+a^2+a^2+a+a+1=\left(a+1\right)\left(a^2+a+1\right)\\ c,=1-4a^2-a\left(a^2-4\right)=1-4a^2-a^3+4a\\ =\left(1-a\right)\left(1+a+a^2\right)+4a\left(1-a\right)\\ =\left(1-a\right)\left(1+5a+a^2\right)\\ d,=\left(a^2-a^2b^2\right)+\left(b^2-b\right)+\left(ab-a\right)\\ =a^2\left(1-b\right)\left(1+b\right)+b\left(b-1\right)+a\left(b-1\right)\\ =\left(b-1\right)\left(-a^2-ab+b+a\right)\\ =\left(b-1\right)\left(b-1\right)\left(a+b\right)\left(1-a\right)\)

\(e,=x^2y+xy^2-yz\left(y+z\right)+x^2z-xz^2\\ =\left(x^2y+x^2z\right)+\left(xy^2-xz^2\right)-yz\left(y+z\right)\\ =x^2\left(y+z\right)+x\left(y-z\right)\left(y+z\right)-yz\left(y+z\right)\\ =\left(y+z\right)\left(x^2+xy-xz-yz\right)\\ =\left(y+z\right)\left(x+y\right)\left(x-z\right)\)

\(f,=xyz-xy-yz-xz+x+y+z-1\\ =xy\left(z-1\right)-y\left(z-1\right)-x\left(z-1\right)+\left(x-1\right)\\ =\left(z-1\right)\left(xy-y-x+1\right)=\left(z-1\right)\left(x-1\right)\left(y-1\right)\)